The Cotton Wall-Associated Kinase GhWAK7A Mediates Responses to Fungal Wilt Pathogens by Complexing with the Chitin Sensory Receptors. Issue 12 (9th October 2020) - Wang, Ping; Zhou, Lin; Jamieson, Pierce; Zhang, Lin; Zhao, Zhixue; Babilonia, Kevin; Shao, Wenyong; Wu, Lizhu; Mustafa, Roma; Amin, Imran; Diomaiuti, Alessandra; Pontiggia, Daniela; et al.
Abstract : GhWAK7A interacts with the GhCERK1-GhLYK5 chitin sensory complex and regulates cotton resistance against fungal diseases. Abstract: Plant receptor-like kinases (RLKs) are important players in response to pathogen infections. Verticillium and Fusarium wilts, caused by Verticillium dahliae ( Vd ) and Fusarium oxysporum f. sp vasinfectum ( Fov ), respectively, are among the most devastating diseases in cotton ( Gossypium spp). To understand the cotton response to these soil-borne fungal pathogens, we performed a genome-wide in silico characterization and functional screen of diverse RLKs for their involvement in cotton wilt diseases. We identified Gossypium hirsutum GhWAK7A, a wall-associated kinase, that positively regulates cotton response to both Vd and Fov infections. Chitin, the major constituent of the fungal cell wall, is perceived by lysin-motif-containing RLKs (LYKs/CERK1), leading to the activation of plant defense against fungal pathogens. A conserved chitin sensing and signaling system is present in cotton, including chitin-induced GhLYK5-GhCERK1 dimerization and phosphorylation, and contributes to cotton defense against Vd and Fov . Importantly, GhWAK7A directly interacts with both GhLYK5 and GhCERK1 and promotes chitin-induced GhLYK5-GhCERK1 dimerization. GhWAK7A phosphorylates GhLYK5, which itself does not have kinase activity, but requires phosphorylation for its function. Consequently, GhWAK7A plays a crucial role in chitin-induced responses. Thus, our data reveal GhWAK7A as an important component in cotton response to fungal wilt pathogens by complexing with the chitin receptors.